The Significance of Doxylamine, an Antihistamine Compound, in the Context of Its Potential Efficacy against COVID-19: Conformational Analysis, Molecular Docking, and Molecular Dynamics Studies - Er, Alev; Önem, Zeynep C.; Çelik, Sefa; Özel, Ayşen E.; AKYÜZ, SEVİM (MAIK Nauka/Interperiodica Publishers/Springer, 2025)
SARS-CoV-2 initiates infection by binding its surface spike glycoprotein to the ACE2 receptor on the human cell surface, facilitating the entry of its genetic material into the human cell. Due to the pivotal role of the spike protein in this infection mechanism, in this study the versatility of the bioactivity of the doxylamine molecule was investigated, and by theoretical molecular modeling studies its potential of blocking the entry of the spike protein into human cells was revealed. In the initial phase of this investigation, conformational analysis of doxylamine was executed employing the PM3 method, yielding six stable conformations. Subsequently, the lowest energy conformation obtained was subjected to optimization at the DFT/B3LYP/6-31++G(d,p) level of theory. Vibrational wavenumbers, highest occupied and lowest unoccupied molecular orbitals, and molecular electrostatic potential for the most stable conformer of doxylamine were computed using the DFT/B3LYP/6-31++G(d,p) level of theory. For docking studies firstly, the optimization by energy minimization feature of the YASARA structure program was employed to both ligand and the ligand-free receptor obtained from the protein databank. Molecular docking simulations were adeptly employed to identify potential compounds with doxylamine anticipated to demonstrate inhibitory activity against the spike protein of SARS-CoV-2. Molecular docking study of doxylamine was conducted with spike receptor-binding domain (RBD) of SARS-CoV-2 (PDB ID: 6M0J). Furthermore, ligand-receptor interactions were scrutinized through a molecular dynamics (MD) simulation lasting 125 ns to verify the stability of doxylamine within the ACE2 binding site.
Keywords: Doxylamine; Molecular Docking; Molecular Dynamics; Vibrational Analysis